Prevalence of asymptomatic malaria, submicroscopic parasitaemia and anaemia in Korogwe District, north-eastern Tanzania - Paul M. Hayuma; Christian W. Wang; Edwin Liheluka; Vito Baraka; Rashid A. Madebe; Daniel T. R. Minja; Gerald Misinzo; Michael Alifrangis; John P. A. Lusingu (Malaria Journal, 2021)
Abstract Background Asymptomatic malaria infections largely remain undetected and act as a reservoir for continuous transmission. The study assessed the prevalence of submicroscopic asymptomatic malaria infections and anaemia in two rural low (300 m above sea level) and highland (700 m asl) settings of Korogwe District north-eastern Tanzania. Methods A cross-sectional malariometric survey involving individuals aged 0–19 years was conducted in June 2018 in the two rural villages. Venous blood was collected from eligible study participants for estimation of haemoglobin level, detection of malaria by rapid diagnostic test (RDT), quantification of malaria parasitaemia by microscopy, as well as dried blood spot (DBS) for determining submicroscopic infections by PCR targeting the small subunit of the ribosomal ribonucleic acid (ssrRNA) of human Plasmodium. Results Out of 565 individuals tested, 211 (37.3%) were malaria positive based on RDT, whereas only 81 (14.3%) were positive by microscopy. There was no significant difference in the prevalence between the highland and the lowland village, p = 0.19 and p = 0.78 microscopy and RDT, respectively. Three out of 206 (1.5%) RDT/microscopy negative samples were P. falciparum positive by PCR. Of the 211 RDT and 81 microscopy positive, 130 (61.6%) and 33 (40.7%), respectively, were defined as being asymptomatic. Of the 565 individuals, 135 (23.9%) were anaemic (haemoglobin < 11 g/dL) out of which 5.2% were severely anaemic. The risk of being anaemic was significantly higher among individuals with asymptomatic malaria as compared to those without malaria as confirmed by RDT (AOR = 2.06 (95% CI 1.32–3.20) while based on microscopic results there was no significant differences observed (AOR = 2.09, 95% CI 0.98–4.47). Age and altitude had no effect on the risk of anaemia even after adjusting for asymptomatic malaria. Conclusions Asymptomatic malaria is associated with an increased risk of having anaemia in the study communities. The findings highlight the need for targeted ...